Psychosocial Aspect in the Acceptance of COVID-19 Vaccines (Systematic Review) (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2021)
COVID-19 vaccine can protect the public and suppress COVID-19 cases. But there are still many people who refuse to be vaccinated. The study aims to analyze the psychosocial aspects in the Acceptance of COVID-19 Vaccines. This study is a systematic review with PRISMA (Preferred Reporting Items for Systematic Reviews & Meta-Analyses). The database used to search data and information is PubMed. The keywords used during the search process are